Factors modulating parental acceptance of SDF treatment. Issue 3 (December 2021) - Bahathiq, Amal; Arafa, Abla
Abstract: Objectives: To assess the degree of parental acceptance of SDF treatment on their children's carious teeth and to explore different factors affecting their decisions. Methods: Parents of healthy children younger than 12-year-old of both gender were asked to fulfill a questionnaire describing their perspective of Silver Diamine Fluoride SDF treatment and different factors that could modify their opinion as sociodemographic characteristics, tooth location, type of dentition, advanced management techniques as well as dental caries management during- and post-COVID pandemic. Participants' responses were categorized according to the three-Point Likert scale as acceptable, neutral, and not acceptable. Fisher test was used to test for significant factors affecting parental acceptance of SDF treatment. The level of significance was tested at 0.05 using SPSS program. Results: A total of 158 parents participated in this study. The parental acceptance of SDF treatment was found to be limited to 31.6%. The SDF acceptance rate increased significantly if SDF was used on posterior teeth, on deciduous dentition, prior to shifting to conventional restoration under general anesthesia, and to minimize chances for cross-infection particularly during- and after the recovery from the COVID pandemic. Conclusions: SDF treatment on posterior teeth and deciduous dentition was found to be more accepted by the parents than anterior and permanent teeth. Although a majority of parents reported restricted SDF treatment acceptance, most parents were willing to compromise the esthetic dilemma as they understand the risks of alternative interventions. Clinical significance: Dentists are encouraged to adopt SDF treatment and offer it for their patients and caregivers prior to shifting to advanced dental management techniques particularly during and following the COVID era. The dentist must provide an informed consent form, which includes clear photographs showing expected staining, especially when treating anterior teeth.